The Evolution of ASEAN International Investment Agreements: Insights from the Past and Future Directions - Anh, Dao Kim (VNU Journal of Science: Legal Studies, 2025)
This article examines the evolution of ASEAN’s international investment agreements (IIAs), highlighting key milestones, challenges, and the distinctive ASEAN Way of treaty-making. From its initial inward-looking agreements in the 1980s to its contemporary focus on regional integration and global outreach, ASEAN’s investment framework reflects a dynamic interplay between regional needs and international best practices. The study traces ASEAN’s transition from fragmented protectionist policies to a progressively liberalized and cohesive investment regime underpinned by four guiding pillars: promotion, protection, facilitation, and liberalization. By analyzing historical and modern IIAs, the article underscores ASEAN’s capacity to strengthen its position as a global investment hub despite challenges posed by economic crises, geopolitical shifts, and the COVID-19 pandemic. Looking forward, the findings suggest that ASEAN must prioritize harmonizing and modernizing its investment instruments, adapting to evolving global trends, and addressing intra-regional disparities to achieve a resilient and competitive investment framework. These insights offer valuable lessons for policymakers and scholars seeking to understand ASEAN’s role in shaping the global investment landscape.